Determination of the Position of the Knee at ACL rupture for Males versus Females by an Analysis of Bone Bruises - Owusu-Akyaw, Kwadwo A. (Am J Sports Med, 2018)
BACKGROUND: The incidence of anterior cruciate ligament (ACL) rupture is 2-4 times higher in female athletes as compared to their male counterparts. As a result, a number of recent studies have addressed the hypothesis that females and males sustain ACL injuries via different mechanisms. The efficacy of prevention programs may be improved by better understanding whether there are differences in injury mechanism between sexes. HYPOTHESIS/PURPOSE: To compare knee positions at the time of non-contact ACL injury between sexes. We hypothesized that there would be no differences in the position of injury. STUDY DESIGN: Descriptive laboratory study. METHODS: Clinical T2 weighted magnetic resonance (MR) images from thirty subjects (15 male and 15 female) with non-contact ACL rupture were reviewed retrospectively. MR images were obtained within 1 month of injury. Subjects had contusions associated with ACL injury on both the medial and lateral articular surfaces of the femur and tibia. Three dimensional models of the femur, tibia, and associated bone bruises were created via segmentation of MR images. The femur was positioned relative to the tibia in order to maximize bone bruise overlap, thereby predicting the bone positions near the time of injury. Flexion, valgus, internal tibial rotation, and anterior tibial translation were measured in the predicted position of injury. RESULTS: No statistically significant differences between males and females were detected in the position of injury with regard to knee flexion (p=0.66), valgus (p=0.87), internal tibial rotation (p=0.26), or anterior tibial translation (p=0.18). CONCLUSION: These findings suggest that a similar mechanism results in ACL rupture in both male and female athletes with this pattern of bone bruising. CLINICAL RELEVANCE: This study provides a novel comparison of male and female knee position at the time of ACL injury that may offer information to improve injury prevention strategies.